Electropulse wells drilling; International Conference on Pulsed Power Applications, Gelsenkirchen, March 29-30, 2001; Vol. 2 - Dulzon A. A. Alfred Andreevich; Vazhov (Vajov) V. F. Vladislav Fedorovich; Zhgun (Jgun) D. V. Dmitry Vladimirovich; Muratov V. M. Vasily Mikhailovich (2001, 2001)
В фонде НТБ ТПУ отсутствует